Emotion graph models for bipedal walk cycle animation - Abdul Rahman, Ayub; Abdul Aziz, Normaziah; Hamzah, Mohd. Syarqawy (2016)
Technology in the animation industry has evolved significantly over the past decade. The tools to create animation are becoming more intuitive to use. Animators now spend more time on the artistic quality of their work than wasting time figuring out how to use the software that they rely on. However, one particular tool that is still unintuitive for animators is the motion graph editor. A motion graph editor is a tool to manipulate the interpolation of the movements generated by the software. Although the motion graph editor contains a lot of options to control the outcome of the animation, the emotional rhythm of the movements desired by the animator still depends on the animator’s skill, which requires a very steep learning curve. More often than not, animators had to resort to trial and error methods to achieve good results. This inevitably leads to slow productivity, susceptible to mistakes, and waste of resources. This research will study the connection between the motion graph profile and the emotions they portray in movements. The findings will hopefully be able to provide animators reference materials to achieve the emotional animation they need with less effort